The Political, Regulatory and Market Failures That Caused the US Financial Crisis - Tarr, David G. (2012)
This paper discusses the key regulatory, market and political failures that led to the 2008-2009 United States financial crisis. While Congress was fixing the Savings and Loan crisis, it failed to give the regulator of Fannie Mae and Freddie Mac normal bank supervisory power. This was a political failure as Congress was appealing to narrow constituencies. In the mid-1990s, to encourage home ownership, the Administration changed enforcement of the Community Reinvestment Act, effectively requiring banks to lower bank mortgage standards to underserved areas. Crucially, the risky mortgage standards then spread to other sectors of the market. Market failure problems ensued as banks, mortgage brokers, securitizers, credit rating agencies, and asset managers were all plagued by problems such as moral hazard or conflicts of interest. The author explains that financial deregulation of the past three decades is unrelated to the financial crisis, and makes several recommendations for regulatory reform.